Evaluation of the Quality of Artemisinin-Based Antimalarial Medicines Distributed in Ghana and Togo. (27th October 2014) - Osei-Safo, Dorcas; Agbonon, Amegnona; Konadu, Daniel Yeboah; Harrison, Jerry Joe Ebow Kingsley; Edoh, Mamadou; Gordon, Andrew; Gbeassor, Messanvi; Addae-Mensah, Ivan
Abstract : This study, conducted as part of our overall goal of regular pharmacovigilance of antimalarial medicines, reports on the quality of 132 artemisinin-based antimalarial medicines distributed in Ghana and Togo. Three methods were employed in the quality evaluation—basic (colorimetric) tests for establishing the identity of the requisite active pharmaceutical ingredients (APIs), semi-quantitative TLC assay for the identification and estimation of API content, and HPLC assay for a more accurate quantification of API content. From the basic tests, only one sample totally lacked API. The HPLC assay, however, showed that 83.7% of the ACTs and 57.9% of the artemisinin-based monotherapies failed to comply with international pharmacopoeia requirements due to insufficient API content. In most of the ACTs, the artemisinin component was usually the insufficient API. Generally, there was a good correlation between the HPLC and SQ-TLC assays. The overall failure rates for both locally manufactured (77.3%) and imported medicines (77.5%) were comparable. Similarly the unregistered medicines recorded a slightly higher overall failure rate (84.7%) than registered medicines (70.8%). Only two instances of possible cross-border exchange of medicines were observed and there was little difference between the medicine quality of collections from border towns and those from inland parts of both countries.